My baby's father : unmarried parents and paternal responsibility - Waller, Maureen Rosamond, 1967- (Cornell University Press, 2002)
About one-third of births in the United States occur to unmarried parents. Evidence suggests that children who grow up in families headed by single parents have worse socioeconomic outcomes than those raised by married parents. "Fatherlessness" has become a byword in public debate and policymaking, yet fundamental questions about unmarried parents and their ideas of paternal responsibility remain unanswered. In My Baby's Father, Maureen R. Waller draws on interviews with unmarried parents whose children receive welfare to address several basic, vital questions: How do low-income mothers and fathers define the father's obligation to his children and explain irresponsible behavior among fathers? How do they negotiate private arrangements of paternal acknowledgment and support? And how do these informal practices interact with mandatory welfare and child-support regulations?The majority of research on low-income families focuses on single mothers. Waller's book also gives a voice to the fathers, historically either excluded from academic and policy discussions or simply characterized as "deadbeat dads" with no sense of paternal responsibility. By documenting the experiences of African-American and white parents simultaneously, Waller illustrates the extent to which beliefs and practices are likely to cut across racial lines. She also shifts the focus from teenagers to adults, who constitute the largest group of unmarried parents. My Baby's Father provides honest glimpses into the lives of unmarried parents. In addition, it offers specific recommendations for social policies that are both better suited to unmarried parents' socioeconomic situations and more responsive to the practices of responsible fatherhood in low-income families